Selection shapes the landscape of functional variation in wild house mice. - Lawal, Raman Akinyanju.; Arora, Uma P.; Dumont, Beth L. (Tufts University. Tisch Library., 2021)
Keywords: Genetic diversity, Mus musculus, Commensalism, Genetic disorder, Mendelian disease, Adaptation, Positive selection, Evolution, Amylase, Metabolism.; Springer Open.